De olhos bem fechados: sexualidade, subjetividades e conjugalidades no swing - Vasconcelos Neto, Edson Peixoto de (2015)
This work consists in the analysis of swing while an event that provides a set of developments related to the subjectivation processes in sexualities and conjugalities in the contemporary world. To do it, I had tried to understand how linked networks are formed to the swing sex from two specific paths: the analysis of on-line sex networks, with a focus on Sexlog (sex social network on the internet); and networks of sex off line, with attention to parties and establishments dedicated to the subject (houses and swing clubs). As one of the main points, "swing" category's labor in Brazil as a generic term used to discuss a set of sexual practices that do not summarize the practice of exchanging couples. It has important consequences, in respect to how this time, the swing event, it makes possible to think of other joints in relation to categories related to swing as the gender, sexuality and the subjectivation processes from those who practices them. In this sense, the swing would be a sexual/social event that would make the suspension or the temporary decrease of moral codes at the same time that would allow the emergence of other desires unlinked to morality, possible made through secret, intimacy and the shuffling points concerning sexuality.